Structural and Magnetic Properties of Biogenic Nanomaterials Synthesized by Desulfovibrio sp. Strain A2 - Mikhail S. Platunov; Yuriy V. Knyazev; Olga P. Ikkert; Olga V. Karnachuk; Anton D. Nikolenko; Roman D. Svetogorov; Evgeny V. Khramov; Mikhail N. Volochaev; Andrey A. Dubrovskiy (Inorganics)
This study explores the phase composition, local atomic structure, and magnetic properties of biogenic nanomaterials synthesized through microbially mediated biomineralization by the sulfate-reducing bacterium Desulfovibrio species strain A2 (Cupidesulfovibrio). Using X-ray diffraction (XRD), transmission electron microscopy (TEM), Mössbauer spectroscopy, X-ray absorption near-edge structure (XANES) spectroscopy, extended X-ray absorption fine structure (EXAFS) spectroscopy, and magnetic measurements, we identified a mixture of vivianite (Fe3(PO4)2·8H2O) and sulfur-containing crystalline phases (α-sulfur). XRD analysis confirmed that the vivianite phase, with a monoclinic I2/m structure, constitutes 44% of the sample, while sulfur-containing phases (α-sulfur, Fddd) account for 56%, likely as a result of bacterial sulfate-reducing activity. X-ray absorption spectroscopy (XAS) and EXAFS revealed the presence of multiple sulfur oxidation states, including elemental sulfur and sulfate (S6+), underscoring the role of sulfur in the sample’s structure. Mössbauer spectroscopy identified the presence of ferrihydrite nanoparticles with a blocking temperature of approximately 45 K. Magnetic measurements revealed significant coercivity (~2 kOe) at 4.2 K, attributed to the blocked ferrihydrite nanoparticles. The results provide new insights into the structural and magnetic properties of these microbially mediated biogenic nanomaterials, highlighting their potential applications in magnetic-based technologies.